Vpliv zaupanja in pripadnosti odnosu na sodelovanje v oskrbovalnih verigah - Mlaker Kač, Sonja (visokošolska dela, 2014)
This dissertation discusses the influence of trust and relationship commitment on collaborative behavior in supply chains. Supply chains are defined as sets of three or more organizations directly involved in (the upstream and downstream) flows of products, services, finances and/or information from a source to a customer and where all companies strive to achieve the same goal. In the theoretical part of the dissertation we presume that the establishment and development of relationships in a supply chain depends on the development of trust and relationship commitment. For the purpose of our work, trust is defined as a willingness to rely on a partner in a supply chain in whom one has confidence. The emphasis is on the expectation that another partner can be relied on to fulfill obligations and at the same time previous experience with partners in exchange relationships is taken in the consideration. Relationship commitment is a term for an exchange partner's belief that an on-going relationship with partners in supply chains is as important as to warrant maximum efforts to maintain it. One of the very important concepts discussed in this dissertation is also collaboration between partners in supply chains. It is defined as a concept where two or more organizations working together in a supply chain, can gain shared means and goals through complementary characteristics that they could not have achieved individually. Collaboration means greater benefits for all partners.
Keywords: collaboration; disertacije; oskrbovalna veriga; pripadnost odnosu; relationship commitment; sodelovanje; supply chain; trust; zaupanje